Mackintosh lecture—: Association and cognition: Two processes, one system. Issue 2 (February 2019) - McLaren, IPL; McAndrew, Amy; Angerer, Katharina; McLaren, Rossy; Forrest, Charlotte; Bowditch, Will; Monsell, Stephen; Verbruggen, Frederick
This article argues that the dual-process position can be a useful first approximation when studying human mental life, but it cannot be the whole truth. Instead, we argue that cognition is built on association, in that associative processes provide the fundamental building blocks that enable propositional thought. One consequence of this position is to suggest that humans are able to learn associatively in a similar fashion to a rat or a pigeon, but another is that we must typically suppress the expression of basic associative learning in favour of rule-based computation. This stance conceptualises us as capable of symbolic computation but acknowledges that, given certain circumstances, we will learn associatively and, more importantly, be seen to do so. We present three types of evidence that support this position: The first is data on human Pavlovian conditioning that directly support this view. The second is data taken from task-switching experiments that provide convergent evidence for at least two modes of processing, one of which is automatic and carried out "in the background." And the last suggests that when the output of propositional processes is uncertain, the influence of associative processes on behaviour can manifest.